Bone substitute materials supplemented with prolyl hydroxylase inhibitors decrease osteoclastogenesis in vitro. Issue 6 (14th October 2014) - Vinzenz, Philipp; Schröckmair, Stefan; Gruber, Reinhard; Agis, Hermann
Abstract Background and objective: Inhibition of prolyl hydroxylases stimulates bone regeneration. Consequently, bone substitute materials were developed that release prolyl hydroxylase inhibitors. However, the impact of prolyl hydroxylase inhibitors released from these carriers on osteoclastogenesis is not clear. We therefore assessed the effect of bone substitute materials that release prolyl hydroxylase inhibitors on osteoclastogenesis. Material and methods: Dimethyloxalylglycine, desferrioxamine, and l‐mimosine were lyophilized onto bovine bone mineral and hydroxyapatite, and supernatants were generated. Osteoclastogenesis was induced in murine bone marrow cultures in the presence of the supernatants from bone substitute materials. The formation of tartrate‐resistant acid phosphatase (TRAP)‐positive multinucleated cells and TRAP activity were determined. To test for possible effects on osteoclast progenitor cells, we measured the effect of the supernatants on proliferation and viability. In addition, experiments were performed where prolyl hydroxylase inhibitors were directly added to the bone marrow cultures. Results: We found that prolyl hydroxylase inhibitors released within the first hours from bone substitute materials reduce the number and activity of TRAP‐positive multinucleated cells. In line with this, addition of prolyl hydroxylase inhibitors directly to the bone marrow cultures dose‐dependently reduced the number of TRAP‐positive multinucleated cells and the overall resorption activity. Moreover, the released prolyl hydroxylase inhibitors decreased proliferation but not viability of osteoclast progenitor cells. Conclusion: Our results show that prolyl hydroxylase inhibitors released from bone substitute materials decrease osteoclastogenesis in murine bone marrow cultures. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1198–1203, 2015.